Childhood Cryptosporidium infection among aboriginal communities in Peninsular Malaysia - Al-Mekhlafi, H.M.; Mahdy, M.A.K.; Azlin, M.Y.; Fatmah, M.S.; Norhayati, M. (2011)
Cryptosporidium is a coccidian parasite that is prevalent worldwide, some species of which cause morbidity in both immunocompromised and immunocompetent individuals. The prevalence and predictors of Cryptosporidium infection, and its effect on nutritional status, have recently been explored among 276 children (141 boys and 135 girls, aged 2-15 years) in aboriginal (Orang Asli) villages in the Malaysian state of Selangor. Faecal smears were examined by the modified Ziehl-Neelsen staining technique while socio-economic data were collected using a standardized questionnaire. Nutritional status was assessed by anthropometric measurements. Cryptosporidium infection, which was detected in 7.2 of the aboriginal children, was found to be significantly associated with low birthweight (<= 2.5 kg), being part of a large household (with more than seven members) and prolonged breast feeding (>2 years). The output of a binary logistic regression confirmed that large household size was a significant predictor of Cryptosporidium infection (giving an odds ratio of 2.15, with a 95 confidence interval of 1.25-5.02). Cryptosporidium infection is clearly a public-health problem among the aboriginal children of Selangor, with person-to-person the most likely mode of transmission.